REVIEW ON MELATONIN IS A NOVEL MOLECULE FOR MANAGEMENT OF VARIOUS DISORDERS - Shivakumar S. Ladde; Bhusnure O. G (Journal of Biomedical and Pharmaceutical Research, 2020)
Melatonin is N-acetyl-5-methoxytryptamine and is an indoleamine. It is synthesized in the pineal gland by the conversion of tryptophan to serotonin, which is acetylated by N-acetyltransferase (NAT) to N-acetyserotonin. N-acetylserotonin is subsequently converted to melatonin by the enzyme hydroxyindole-omethyltransferase. Melatonin receptors are G-protein coupled receptors and mainly classified into MT1 (Mel1a) and MT2 (Mel1b). Melatonin is an ubiquitous molecule, which has been found not only in the human pineal gland but also in vegetables and their fruits and seeds, medicinal herbs, and fermented products such as Piper nigrum, cherry, Kiwifruit, grapes, walnut, etc. In the present research we review the beneficial effect of Melatonin for management of various disorders on basis literature survey available on PubMed, science direct, magazine, e-journal, etc. From the review it conclude that the melatonin has been assessed as a treatment of ocular diseases, blood diseases, gastrointestinal tract diseases, cardiovascular diseases, diabetes, rheumatoid arthritis, fibromyalgia, chronic fatigue syndrome, infectious diseases, neurological diseases, sleep disturbances, aging and depression. Melatonin has been also used as a complementary treatment in anaesthesia, hemodialysis, in vitro fertilization and neonatal care. In the future, analogues of melatonin may be of value in treating various chronic disorders. Keywords: Melatonin, N-acetylserotonin, Piper nigrum, Diabetes, Depression, Hemodialysis